UPAYA PENINGKATAN KOMPETENSI GURU DALAM MENYUSUN SILABUS DAN RPP MELALUI SUPERVISI AKADEMIK YANG BERKELANJUTAN DI SMP NEGERI 3 MUARA BUNGO - Marief Arief (LP3M STKIP Muhammadiyah Muara Bungo, 2021)
A teacher is required to plan, implement and evaluate learning. The same thing happens with the teaching and learning process in schools that must have a plan. This research includes five elements, namely; make annual programs, make syllabus, make semester programs, make lesson plans, and make test or evaluation programs. This study aims to make efforts to improve teacher competence at SMP Negeri 3 Bungo and to see to what extent the principal's academic supervision steps can improve teacher competence in the preparation of syllabus and lesson plans. Based on the results of the analysis in the 2018/2019 academic year at SMP Negeri 3 Bungo, there was a problem with the low number of teachers who made lesson plans, especially the preparation of syllabus and lesson plans.